Risk factors associated with post-tuberculosis sequelae: a systematic review and meta-analysisResearch in context - Temesgen Yihunie Akalu; Archie C.A. Clements; Alemneh Mekuriaw Liyew; Beth Gilmour; Megan B. Murray; Kefyalew Addis Alene (EClinicalMedicine)
Summary: Background: Post-tuberculosis (TB) sequelae present a significant challenge in the management of TB survivors, often leading to persistent health issues even after successful treatment. Identifying risk factors associated with post-TB sequelae is important for improving outcomes and quality of life of TB survivors. This systematic review and meta-analysis aims to identify risk factors associated with long-term physical sequelae among TB survivors. Methods: We systematically searched Medline, Embase, PROQUEST, and Scopus for studies on long-term physical sequelae among TB survivors up to December 12, 2023. The primary outcome of interest was to quantify risk factors of long-term physical sequelae (i.e., respiratory, hepatic, hearing, neurological, visual, renal, and musculoskeletal sequelae). We included all forms of TB patients who experienced long-term physical sequelae. We used narrative synthesis for risk factors reported once and random-effect meta-analysis for primary outcomes with two or more studies. Findings were presented with odds ratios (OR) and 95% confidence intervals (CI). Publication bias was assessed using funnel plots and Egger regression, and heterogeneity was examined with a Galbraith radial plot. The protocol was registered on Prospero (CRD42021250909). Findings: A total of 73 articles from 28 countries representing 31,553 TB-treated patients were included in the narrative synthesis, with 64 of these studies included in the meta-analysis. Risk factors associated with post-TB lung sequelae include older age (OR = 1.62, 95% CI: 1.07–2.47), previous TB treatment history (OR = 3.43, 95% CI: 2.37–4.97), smoking (OR = 1.41, 95% CI: 1.09–1.83), alcohol consumption (OR = 1.84, 95% CI: 1.04–3.25), smear-positive pulmonary TB diagnosis (OR = 3.11, 95% CI: 1.77–6.44), and the presence of radiographic evidence of pulmonary lesions at the commencement of treatment (OR = 2.04, 95% CI: 1.07–3.87). Risk factors associated with post-TB liver injury included pre-existing hepatitis (OR = 2.41, 95% CI: 1.16–6.08), previous TB treatment (OR = 2.64, 95% CI: 1.22–6.67), hypo-albuminemia (OR = 2.10, 95% CI: 1.53–2.88), HIV co-infection (OR = 2.72, 95% CI: 1.66–4.46), and CD4 count <200 mm3 in HIV-infected individuals (OR = 2.03, 95%CI: 1.26–3.27). Risk factors associated with post-TB hearing loss include baseline hearing problems (OR = 1.72, 95% CI: 1.30–2.26), and HIV co-infection (OR = 3.02, 95% CI: 1.96–4.64). Interpretation: This systematic review and meta-analysis found that long-term physical post-TB sequelae including respiratory, hepatic, and hearing impairment were associated with a range of socio-demographic, behavioral, and clinical factors. Identification of these risk factors will help to identify patients who will benefit from interventions to reduce the burden of suffering from post-TB treatment. Funding: Healy Medical Research Raine Foundation, the Australian National Health and Medical Research Council, and Curtin University Higher Degree Research Scholarship fund the study.